Enhancement of outage probability for down link cooperative non-orthogonal multiple access in fifth-generation network - Mohamed Hassan; Manwinder Singh; Khalid Hamid; Imadeldin Elsayed Elmutasim (Institute of Advanced Engineering and Science, 2023)
Future wireless networks are expected to face several issues, but cooperative non-orthogonal multiple access (C-NOMA) is a promising technology that could help solve them by providing unprecedented levels of connection and system capacity. In this regard, the influence of the power location coefficient (PLC) for remote users adopting multiple-input-multiple-output (MIMO) and massive MIMO has been explored to provide effective performance. The goal of this study is to design fifth-generation (5G) downlink (DL) NOMA power domain (PD) networks with a variety of distances and PLCs for remote users and then to compare their outage probability (OP) performance versus signal to noise ratio (SNR). As a novel approach to improving OP performance rate and mitigating the influence of the PLC for remote users, DL C-NOMA is combined with 16×16, 32×23, and 64×64 MIMO and 128×128, 256×256, and 512×512 massive MIMO. The results were obtained that the 64×64 MIMO improves the OP for the remote user by 65.0E-03, while the 512×512 massive MIMO achieved an improvement that reaches 1.0E-06 for the PLC of 0.8 at SNR of 14 dB. The Rayleigh fading channels and MATLAB simulation tools were utilized to carry out the study work.